Penggunaan Fiber Reinforced Composite sebagai Resin Bonded Prosthesis pada Gigi Anterior - Hastoro Pintadi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
Resin bonded prosthesis is a fixed bridge which replace a space where one or two teeth have been lost or extracted, by using acid etched technique and resin bonding. The main goals in selecting a Resin bonded prosthesis were to preserve tooth structure, maintain esthetics and lower patient fees while providing restorations that had the potential for long-term service. This case report discuss about fiber reinforced composite used as a main material for resin bondedprosthesis to replace incivus lateralis maxillary that has lost The successfullness of this treatment depend on the case selection and the retention.Resin bondedprosthesis merupakan gigi tiruan cekat yang menggantikan satu atau dua gigi yang hilang dengan menggunakan teknik etsa asam dan ikatan resin. Tujuan utama pemilihan resin bondedprosthesis adalah untuk mendapatkan restorasi jangka panjang yang mampu menjaga struktur gigi penyangga, mendapatkan estetik yang baik, dengan biaya rendah. Laporan kasus ini membahas mengenai fiber reinforced composite sebagai bahan resin bondedprosthesis untuk menggantikan gigi incisivus lateralis kiri atas yang telah hilang. Keberhasilan perawatan ini tergantung pada seleksi kasus dan retensi yang dihasilkan.